PENGARUH TEKNOLOGI INFORMASI DAN BUDAYA ORGANISASI TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI Studi pada PT. Indonesia Power UPJP Kamojang - Yuni Marginingsih (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2018)
This study aims todetermine howmuch influence of information technology and organizational culture on the quality of accounting information systems.The research methode used is descriptive methode. Sampling taken as many as 38 employees, taken fromthe total population as many as 40 employees. Test tool of this research with questionnaire. The test uses validity test, reliability test,classical assumption test,multipe linear regression analysis, correlation test, multiple linear regression analysis,correlation analysis, determination coefficient analysis and t test using SPSS software version 23.0 From results of research based on coefficient of determination obtained there is a strong in fluence of information technology on the quality of accounting information system of 57.76%. While there is a low influence of organizational culture on accounting information system quality of 47.77%, and the rest influenced by other factors.